The distribution of Labdane Diterpenes in the Zingiberaceae of Malaysia - M. Sirat, Hasnah; Masri, Dian; A. Rahman, Ahmad (Elsevier Science, 1994)
Labda-8(17),12-diene-15,16-dial and coronarin E were isolated from the chloroform extract of the rhizomes of Alpinia javanica. The structures were elucidated spectroscopically. This is the first report of the isolation of coronarin E from Alpinia species. The distribution of these two labdane diterpenes within the Zingiberaceae is reported.